The politicians' wage gap: Insights from German members of parliament - Andreas Peichl; Nico Pestel; Sebastian Siegloch (Institute for the Study of Labor (IZA), 2011)
Using a unique dataset of German members of parliament with information on total earnings including outside income, this paper analyzes the politicians' wage gap (PWG). After controlling for observable characteristics as well as accounting for selection into politics, we find a positive PWG which is statistically and economically significant. It amounts to 40-60% compared to citizens with an executive position. Hence, we show that the widely held claim that politicians would earn more in the private sector is not confirmed by our data. Our findings are robust with respect to potential unobserved confounders. We further show that the PWG exceeds campaigning costs and cannot be justified by extraordinary workload. Hence, our results suggest that part of the PWG can be interpreted as rent extraction. This calls for a reform of the regulation of outside earnings, which account for a sizeable share of the wage premium.
urn:nbn:de:101:1-201104113934
Keywords: D72; H11; H83; J31; J45; 330; politicians' wage gap; descriptive representation; citizen-candidate model; political rents; outside earnings; Politiker; Nebentätigkeit; Lohndrift; Rent Seeking; Deutschland